A disproportionality analysis of FDA adverse event reporting system (FAERS) events for ticagrelor - Pan, Yunyan; Wang, Yu; Zheng, Yifan; Chen, Jie; Li, Jia (Frontiers in Pharmacology, 2024)
Background: Ticagrelor is a commonly used antiplatelet agent, but due to the stringent criteria for trial population inclusion and the limited sample size, its safety profile has not been fully elucidated.We utilized OpenVigil 2.1 to query the FDA Adverse Event Reporting System database and retrieved reports by the generic name "ticagrelor" published between 1 October 2010 and 31 March 2023. Adverse drug events (ADEs) were classified and described according to the preferred terms and system organ classes in the Medical Dictionary of Regulatory Activity. Proportional reporting ratio (PRR), reporting odds ratio (ROR) and Bayesian Confidence Propagation Neural Network (BCPNN) were used to detect signals.